Familial hemiplegic migraine CaV2.1 channel mutation R192Q enhances ATP-gated P2X3 receptor activity of mouse sensory ganglion neurons mediating trigeminal pain - Nair Asha; Simonetti Manuela; Birsa Nicol; Ferrari Michel D; van den Maagdenberg Arn MJM; Giniatullin Rashid; Nistri Andrea; Fabbretti Elsa (SAGE Publishing, 2010)
Abstract Background The R192Q mutation of the CACNA1A gene, encoding for the α1 subunit of voltage-gated P/Q Ca2+ channels (Cav2.1), is associated with familial hemiplegic migraine-1. We investigated whether this gain-of-function mutation changed the structure and function of trigeminal neuron P2X3 receptors that are thought to be important contributors to migraine pain. Results Using in vitro trigeminal sensory neurons of a mouse genetic model knockin for the CACNA1A R192Q mutation, we performed patch clamp recording and intracellular Ca2+ imaging that showed how these knockin ganglion neurons generated P2X3 receptor-mediated responses significantly larger than wt neurons. These enhanced effects were reversed by the Cav2.1 blocker ω-agatoxin. We, thus, explored intracellular signalling dependent on kinases and phosphatases to understand the molecular regulation of P2X3 receptors of knockin neurons. In such cells we observed strong activation of CaMKII reversed by ω-agatoxin treatment. The CaMKII inhibitor KN-93 blocked CaMKII phosphorylation and the hyperesponsive P2X3 phenotype. Although no significant difference in membrane expression of knockin receptors was found, serine phosphorylation of knockin P2X3 receptors was constitutively decreased and restored by KN-93. No change in threonine or tyrosine phosphorylation was detected. Finally, pharmacological inhibitors of the phosphatase calcineurin normalized the enhanced P2X3 receptor responses of knockin neurons and increased their serine phosphorylation. Conclusions The present results suggest that the CACNA1A mutation conferred a novel molecular phenotype to P2X3 receptors of trigeminal ganglion neurons via CaMKII-dependent activation of calcineurin that selectively impaired the serine phosphorylation state of such receptors, thus potentiating their effects in transducing trigeminal nociception.